The impacts and conflicts associated with defunct gold tailings storage facilities in South Africa: A case study of Davidsonville, Central Rand - Nwaila, Phumzile Cynthia (Department of Chemical Engineering, 2021)
Gold mining generates large quantities of tailings waste. These tailings can have a significant negative impact on the surrounding environment, with concomitant effects on local ecosystems, as well as on human health and quality of livelihoods. The latter is a concern in the Witwatersrand goldfields of South Africa, where communities are located in close proximity to gold mining operations and/or both current and defunct tailings dumps. This research project was, therefore, aimed at developing a better understanding of the facts, perceptions, concerns, and expectations associated with Witwatersrand gold mine tailings storage facilities, and how these are related. In order to fulfil this aim, a desktop study was conducted which involved a detailed review of published academic literature, company reports, newspaper articles, gold mining magazines, and specialist reports with specific emphasis placed on the Central Rand goldfields of the Witwatersrand Basin. Semi-structured interviews were also conducted with representatives from the community, civil society organisations and independent experts, using the defunct Princess gold tailings dump in Davidsonville Suburb (West of Johannesburg) as a case study. The literature review of the study has shown that there is environmental pollution (air, water and soil) due to gold tailings dumps in current and historic gold mining areas. These findings were found to be largely consistent with perceptions and concerns of the community members, civil society organisations and subject matter experts. The long-term impacts of this pollution are not only environmental but cause a huge social burden on health and quality of livelihoods. Not only is dust considered a nuisance, particularly in the windy season, but the dust has been proven to contain crystalline silica and radionuclides. The long-term exposure to this dust can lead to skin problems and respiratory illnesses. There is higher exposure of ambient particulate matter (PM10) in areas around tailings even at distances up to 2 km downwind from the tailings dumps. Acid mine drainage, on the other hand, increases metal load in watercourses and soils, ultimately affecting the ecosystems as the metals are toxic to plants. Metal contamination has adverse impacts on animal and human health. In addition to literature survey, results from the semi-structured interviews revealed that there are conflicts between the communities, government and mining companies, with communities associating their health problems with gold mine tailings. This has led to court cases and gained media attention. The complex relationships between mine waste, the environment, and community health and livelihoods are still not well understood, making it difficult to justify and motivate the implementation of meaningful interventions to mitigate risks associated with gold tailings dumps. To date, little attempt appears to have been made to support community concerns and perceptions with factual evidence and information. Overall, this study has demonstrated the existence of longstanding issues associated with defunct gold tailings dumps and the communication gab that existing between various stakeholders, i.e. community, government and mining houses. These emphases the importance of having adequate remedial actions to prevent further pollution, the need to engage all relevant stakeholders when dealing with gold tailings and implementation of regulatory frameworks associated with gold tailings reclamation and rehabilitation.